2022
DOI: 10.1038/s41598-022-14430-4
|View full text |Cite
|
Sign up to set email alerts
|

σ-Aromaticity in planar pentacoordinate aluminium and gallium clusters

Abstract: Planar hypercoordinate structures are gaining immense attention due to the shift from common paradigm. Herein, our high level ab initio calculations predict that planar pentacoordinate aluminium and gallium centres in Cu5Al2+ and Cu5Ga2+ clusters are global minima in their singlet ground states. These clusters are thermodynamically and kinetically very stable. Detailed electronic structure analyses reveal the presence of σ-aromaticity which is the driving force for the stability of the planar form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…27,28 Inspired by the achievement of the novel planar hypercoordinate carbon chemistry, people have shown great interest in the possibilities of the other main group elements for planar hypercoordination. [29][30][31][32] As the boron atom is electron deficient in nature, some ionic states of boron clusters and boron-rich systems contain a planar hypercoordinate boron center. In 2004, Li et al explored the PES of the BCu 5 H 5 À system and found planar pentacoordinate boron (ppB) in the global minimum structure having a D 5h point group of symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Inspired by the achievement of the novel planar hypercoordinate carbon chemistry, people have shown great interest in the possibilities of the other main group elements for planar hypercoordination. [29][30][31][32] As the boron atom is electron deficient in nature, some ionic states of boron clusters and boron-rich systems contain a planar hypercoordinate boron center. In 2004, Li et al explored the PES of the BCu 5 H 5 À system and found planar pentacoordinate boron (ppB) in the global minimum structure having a D 5h point group of symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical bonding descriptors provide a valuable tool for understanding the electronic structure and interatomic interactions in different molecular systems. Chemical bond analysis can support both experimental and computational results, providing insights into the effect of the chemical environment on atomic interactions. Among the various chemical bond models available, the quantum theory of atoms in molecules (QTAIM), energy decomposition analysis (EDA), electron localized function (ELF), and natural bond orbitals (NBOs) are widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Planar hepta- and octacoordinate boron (p7B, p8B) centers can be stabilized in the beautiful molecular wheels B 8 − and B 9 − , which were experimentally observed by Zhai in 2003 [ 28 ]. The wheel-like ppB B 6 H 5 + , ppBe BeCu 5 , p8Be BeB 8 2− , p7Sc ScCu 7 , ppAl Cu 5 Al 2+ , ppGa Cu 5 Ga 2+ , and star-like ppB BBe 5 Au 5 , phGa GaBe 6 Au 6 were identified as the global minima [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Using size-selected anion photoelectron spectroscopy combined with ab initio calculations, a series of transition-metal-centered monocyclic boron wheel clusters M©B n ( n = 8–10) were reported by Wang and Boldyrev [ 36 ].…”
Section: Introductionmentioning
confidence: 99%